On the development of family relations of different generations in Uzbekistan - Akramova E.I. (Zien Journals, 2022)
This article analyzes family relations of different generations in Uzbek families, examines the dynamics of relations, the preservation of traditions and customs in Uzbekistan
Keywords: Traditions; customs; Uzbek people; development